Caking of spray-dried avocado powder - Santos, Sérgio C.S.; Cal-Vidal, José (Pesquisa Agropecuaria Brasileira, 2014)
The caking condition or nonflow limit of spray-dried avocado powder was determined for several environmental conditions of temperature (7°C to 45°C), relative humidity (30% to 76%). besides water content and the use of body substances (lactose, carboxy-methyl-cellulose (CMC) and corn starch). Such condition was greatly affected by the environment temperature and relative humidity, with critical values found for these variables from which their effect on the degree of caking changes drastically. The water content of the samples also plays an important role on the nonflow condition, which becomes significant as temperature increases. While the addition of lactose and corn starch unexpectedly had a negative effect in depressing the degree of caking, CMC presented a nonsignificant effect on that property.
Keywords: nonflow limit; water content; lactose; corn starch